Numerical Simulation For Free Convection In Axisymmetric Porous Medium - Chan, Kien Wing (Universiti Sains Malaysia, 2005)
Computational finite element method employing Galerkin’s method of weighted residuals has been used to analyze free convection heat transfer in axisymmetric porous medium saturated by fluid. The approach is used to study the effect of aspect ratio (0.6 – 8), radius ratio (0.1 – 10) and Rayleigh number range from 10 – 100 on the average Nusselt number, Nu in the case of porous cylindrical annulus. Three cases are studied here: isothermal wall temperature, power law temperature variation on both inner or outer wall and convective boundary on outer wall. The power law index for the power law temperature variation is ranges from 0.25 – 1.00. With convective boundary at the outer wall of the axisymmetric porous medium, heat transfer coefficient of 0.01 – 100 (W/m2 .K) is taken into the study for the effect on the average Nusselt number.